2015
DOI: 10.1080/10810730.2015.1018575
|View full text |Cite
|
Sign up to set email alerts
|

Mass Media and HIV/AIDS Prevention Among Female Sex Workers in Beijing, China

Abstract: The current study aimed to identify the sources of HIV prevention information for female sex workers in Beijing and assess the associations between levels of mass media exposure of HIV/AIDS prevention information and HIV/AIDS knowledge as well as condom use–related attitudes, beliefs, and behaviors. Cross-sectional data were collected from 359 female sex workers in Beijing, China. Chi-square tests and one-way ANOVA tests were employed. Female sex workers sampled in Beijing were more likely to obtain HIV/AIDS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…This is consistent with previous studies that reported mass media as one of the important sources of HIV/AIDS information in terms of prevention and decreasing stigmatizing behaviors [23,27,28]. Therefore, collaboration between the media companies and the various governmental and non-governmental organizations in Ghana to intensify HIV/AIDS messages to youth and to the entire Ghanaian population is highly recommended.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous studies that reported mass media as one of the important sources of HIV/AIDS information in terms of prevention and decreasing stigmatizing behaviors [23,27,28]. Therefore, collaboration between the media companies and the various governmental and non-governmental organizations in Ghana to intensify HIV/AIDS messages to youth and to the entire Ghanaian population is highly recommended.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically designed programs could be initiated for targeting both the agents of stigmatization and the stigmatized. According to Xiao and colleagues [28] and Singhal and Rogers [30], mass media, especially television, is a powerful medium for communicating sensitive health messages as well as being able to effectively change health behaviors in individuals with low literacy levels who otherwise might find it difficult to process such messages. Health messages should be available and reinforced in already existing informal gatherings such as youth centers, churches, and community and market gatherings to help young women acquire the right HIV/AIDS knowledge for self-protection as well as acceptance of peers who are infected with the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Radio, television, and newspaper advertisements have helped to raise awareness on HIV prevention for women of reproductive age, which has likely improved consistent condom use. 20 , 21 Perhaps, increased exposure to media sources or outreach programs fostered a greater awareness on the importance of using condoms consistently to prevent HIV among FSW in our sample. Other factors, however, may explain the decline in HIV and syphilis we observed, such as increased availability of treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Internationally, eHealth interventions have shown promise to promote health and safety among Internet-based sex workers [ 14 , 15 ]. Minimal attention has been paid in Canada, however, to developing interventions tailored to this population.…”
Section: Introductionmentioning
confidence: 99%